Bioinformatics-driven identification of key non-invasive prognostic biomarkers in hepatocellular carcinoma - Muhammad-Redha Abdullah-Zawawi; Muhammad Irfan Abdul Jalal; Shing Cheng Tan; Loscheni Varma; Nur Alyaa Afifah Md Shahri; Mira Farzana Mohamad Mokhtar; Ryia Illani Mohd Yunos; Nurul Syakima Ab Mutalib; Rahman Jamal (Egyptian Journal of Medical Human Genetics)
Abstract Background Hepatocellular carcinoma is a highly encountered primary liver malignancy, currently ranked as the third major contributor to death worldwide. This research endeavoured to establish non-invasive prognostic determinants of hepatocellular carcinoma (HCC) and characterise their underpinning molecular mechanisms. Methods Publicly available microarray data within the Gene Expression Omnibus repository were analysed to determine genetic elements that were differentially expressed. We subsequently developed a network of protein–protein interactions and established the densely interconnected clusters (core genes) underlying the network using these differentially expressed genes (DEGs). The prognostic significance of individual core gene was characterised by evaluating its impact on overall survival in HCC. The levels of expression of these core genes underwent further verification from a proteomic perspective by utilising The Human Protein Atlas (HPA) and evaluated for their link with immune cell trafficking within HCC tissues. Results Four core genes (GTF2H1, SF3A3, FANCI, and XRCC5) were identified, which have been associated with HCC and play significant roles in immune cell trafficking through a positive correlation with neutrophils, dendritic cells, and macrophages. Furthermore, GTF2H1 exhibited positive correlations with genetic markers of M1 macrophages (IRF5), dendritic cells (NRP1), and Th1 cells (STAT1); SF3A3 with dendritic cells (NRP1) and PDL1 (CD274); FANCI with M1 macrophages (IRF5); and XRCC5 with PDL1 (CD274) and Th1 cells (STAT1), implying that these core genes might influence or be involved in immune response pathways by promoting immune cell activity. Using the HPA protein expression database, immunohistochemistry findings reaffirmed that the four genes’ expressed protein levels were more elevated in HCC than in healthy hepatocytes. Conclusion Our prognostic signature and immune infiltration provided novel insights into prognostic indicators and potential immunotherapeutic targets for HCC. Future research endeavours are warranted to explore further the clinical importance, applicability, and therapeutic consequences of the identified biomarkers in larger cohorts.